Evaluation of Glycemic Index of Selected Black Rice Cultivars in Bangladesh: Evaluation of glycemic index of selected local rice cultivars in Bangladesh (Journal of the Bangladesh Agricultural University, 2024)
The Glycemic Index (GI) helps consumers select foods with a low GI, which can reduce the risk of diabetes. An in vivo investigation was conducted to screen for optimal glycemic index (GI) content rice varieties suitable for regular diets, particularly for individuals managing diabetes mellitus. Ten healthy volunteers with no diabetes participated in the study, consuming glucose as a reference food and various rice cultivars after overnight fasting. The rice cultivars included black rice from Indonesia, the Philippines, and Vietnam, along with ACI rice serving as the control. Proximate analysis assessed moisture, fat, fiber, protein, ash, and carbohydrate content in all rice samples. Amylose content (%) was determined using spectrophotometric analysis following alcoholic-alkaline gelatinization, acidification, and iodine mixing. The results indicated GI values of 67.23, 54.19, 52.64, and 53.50, and amylose content (%) of 19.42, 21.77, 28.50, and 27.52 for Indonesia line, Philippines line, Vietnam line, and ACI rice, respectively. An inverse relationship between GI levels and amylose content was observed, suggesting a potential mechanism for regulating postprandial blood glucose levels. Based on the findings, the Philippines line and Vietnam line were classified as low-GI rice varieties, indicating their suitability for regular consumption by individuals with diabetes mellitus or without the condition. These results underscore the importance of selecting appropriate rice varieties to manage glycemic response effectively in dietary management strategies for diabetes mellitus. Further research is warranted to explore the underlying mechanisms and to validate these findings in larger cohorts.J Bangladesh Agril Univ 22(2):249-256, 2024